Emerging successes and persistent challenges in Hungarian minority education in Romania - Tódor, Imre (Central European Journal of Educational Research, 2025)
This study examines the early impacts of recent curriculum and examination reforms in Romanian minority education, focusing on the introduction of the “Romanian as a non-native language” curriculum for Hungarian-speaking students. Using aggregated national assessment and baccalaureate data from 2020–2025, the research analyzes trends in Romanian language performance among minority students, compares results across regions and school types, and uses mathematics performance as a comparative indicator to contextualize language-specific achievement patterns. Descriptive, cohort-comparative, and proportion-difference analyses, complemented by hypothetical “what-if” calculations, reveal that while a persistent 1.3–1.5 point gap remains between minority and majority students in Romanian language performance at the 8th-grade level, mathematics scores are nearly equivalent, indicating that the gap is linguistic rather than cognitive. In the 2025 baccalaureate – the first year of full curriculum implementation – pass rates improved notably in high-minority regions (e.g., Harghita +5.3 pp, Covasna +1.6 pp), alongside a significant reduction in failure rates, particularly in vocational and technical schools. The findings suggest that aligning examination content with a differentiated curriculum may be associated with more favorable educational outcomes among minority students, though effectiveness varies by region and school type. Sustainable gains require targeted teacher training, adequate resources, and systematic monitoring to address persistent structural and contextual disparities.